2016
DOI: 10.1590/s1980-6574201600020009
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative evaluation of trunk muscle strength in wheelchair basketball players

Abstract: Abstract--Trunk muscle strength affects trunk controlling playing an important role in performance and to define the classes of wheelchair basketball players. Trunk control capacity differs among players and quantitative assessments of trunk muscle strength have not been investigated. The aim of this study was to identify and correlate quantitative measures of trunk muscle strength with the wheelchair basketball players' classification. Forty-two male wheelchair basketball players with spinal cord injury, ampu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Although BID is a gold standard for biomechanical data measurement [41], the small number of studies in Paralympic fields shows a lack of scientists' interest to use the method in their studies. Among the included studies, 50% were performed in Brazil in years 2015-2018 [32][33][34][35][36], which indicates a tendency of Brazilian researchers to investigate this topic to a higher degree than in the case of other countries, particularly in the recent years.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although BID is a gold standard for biomechanical data measurement [41], the small number of studies in Paralympic fields shows a lack of scientists' interest to use the method in their studies. Among the included studies, 50% were performed in Brazil in years 2015-2018 [32][33][34][35][36], which indicates a tendency of Brazilian researchers to investigate this topic to a higher degree than in the case of other countries, particularly in the recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Five studies were accomplished in Brazil [32][33][34][35][36], 2 in the Netherlands [37,38], 1 in the United states [39], 1 in Poland [25], and 1 in New Zealand [40]. the total number of participants in the 10 studies was 219, with 149 being para-athletes; the size of the sample ranged from 4 to 42 subjects.…”
Section: Characterization Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…As critical as this skill is to wheelchair users, very little research has been conducted on this aspect of wheelchair mobility, particularly with respect to functional capacity. Seated balance is impaired in wheelchair users across a functional spectrum [5], and this is demonstrated by the high incidence of falls in this population. In one study of 659 wheelchair users, 31% reported a total of 553 fall events, with 15% of these occurring during wheelchair propulsion [6].…”
Section: Introductionmentioning
confidence: 99%